The properties and biodegradability of PCL/PLA blends - Lee, MJ; Lee, MC; Shin, PK (POLYMER SOC KOREA, 1998)
To study the change of tensile strength, elongation property, thermodynamic behavior, water-absorption property, and biodegradability of PCL/PLA blends, PCL/PLA = 100/0, 80/20, 60/40, 50/50, 40/60, 20/80, and 0/100 specimens were prepared. The biodegradability tests were performed by measuring the CO2 quantities evolved from incubators containing activated sludge. The experimental results show that the tensile strength, elongation and biodegradability increase as the quantity of PCL increases, while the rate of water-absorption decreases. The thermodynamic behaviors studied using DSC show that the PCL and PLA are not compatible.